Estrategias de gestión cultural, instituciones públicas y la promoción de la cultura montuvia en la Provincia de Los Ríos - ARANA AÑAPA, SENDY PAULINA (2024)
The present investigative work focuses on the cultural management of the Montuvian culture in the Province of Los Ríos. Through this study, the strategies implemented by public institutions for the promotion and dissemination of montuvia conservation are explored. Through a descriptive and inductive approach, data is collected using the interview technique, in order to investigate the perceptions of cultural management professionals and others involved, about how the montuvia culture is being promoted and disseminated. This work seeks to contribute to the understanding and appreciation of cultural diversity, as well as the strengthening of the Montuvian identity and cultural heritage of the province of Los Ríos. By addressing these aspects, the aim is to promote the sustainable development of Montuvian communities and promote greater recognition of their contribution to cultural wealth. The analysis of cultural management and promotion of Montuvia culture in Los Ríos can serve as a basis for future research and actions aimed at preserving and disseminating the unique cultural expressions of this community.